A rapid preparation method and application of calcium ion-doped porous ruthenate pyrochlore catalyst

A porous ruthenate pyrochlore catalyst was prepared through calcium ion doping and Joule heat treatment technology, which solved the problems of difficult catalyst sintering and component modulation in traditional methods, and achieved efficient acidic OER performance and low-cost preparation.

CN118792694BActive Publication Date: 2025-01-21SHANDONG HAIHUA GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411264329.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-21
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The existing ruthenate calcinite catalyst is sintered at high temperature, resulting in a decrease in specific surface area, unstable catalytic activity, and difficult component modulation, which limits its application in acidic OER.

Method used

A rapid preparation method of calcium ion-doped porous ruthenate pyrochlore catalyst is used to form a gel through a stirring reaction at 70-95°C, then mixed with nano-calcium carbonate and subjected to Joule heat treatment, and finally treated in an acetic acid aqueous solution to Form a porous structure.

Benefits of technology

It effectively inhibits the sintering of ruthenate pyrochlore, forms a high specific surface area and rich porous structure, improves the acidic OER performance of the catalyst, and reduces preparation costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118792694B_ABST
    Figure CN118792694B_ABST
Patent Text Reader

Abstract

The present invention provides a rapid preparation method and application of a porous ruthenate pyrochlore catalyst doped with calcium ions, and belongs to the field of electrochemical technology. The present invention first forms a gel material through a metal salt complex reaction, and then uses a nano-calcium carbonate additive to assist the Joule heat treatment technology to prepare a porous ruthenate pyrochlore catalyst doped with calcium ions. This preparation method can inhibit the aggregation of ruthenate pyrochlore at high temperature, form a rich pore structure, promote calcium ions to enter the lattice of ruthenate pyrochlore, effectively modulate the composition of ruthenate, optimize the geometric configuration and electronic structure of Ru in the ruthenate catalyst, enhance the intrinsic activity of Ru, and show excellent acidic OER performance. In 0.1M HClO4 aqueous solution, 10 mA·cm ‑2 Under the current density, the OER overpotential of the catalyst is 202.1-235.4mV, which exceeds the commercial IrO2 under the same conditions, and has broad prospects for industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a rapid preparation method and application of a calcium ion-doped porous ruthenate pyrochlore catalyst, belonging to the technical field of electrochemistry. Background Art

[0002] The oxygen evolution reaction (OER) plays an important role in both hydrogen production from water electrolysis and power generation from regenerative fuel cells. Current OER catalysts are still constrained by their slow reaction kinetics and instability in acidic media. Compared with alkaline systems, acidic systems have higher ionic conductivity and fewer side reactions, and are generally more suitable for OER reactions. However, acidic OER catalysts are still mainly based on classic RuO2 and IrO2, but their high prices and limited reserves limit their feasibility in large-scale commercial applications. Therefore, it is of great significance to develop an OER catalyst suitable for acidic media.

[0003] Ruthenate pyrochlore is a candidate material to replace iridium oxide as an electrocatalyst for the oxygen evolution reaction (OER), but high temperature (≈1100℃) and long calcination time (more than 12h) hinder its composition modulation and reduce its technical and economic feasibility. At the same time, high temperature will bring obvious sintering phenomenon, which seriously affects its specific surface area, intrinsic activity, etc. Therefore, the development of a fast, low-cost ruthenate pyrochlore that can inhibit sintering, increase its specific surface area, and optimize its composition is not only of great significance for improving the performance of OER catalysts and reducing the cost of water electrolysis, but also has a far-reaching impact on promoting the development and application of renewable energy technologies.

[0004] The Chinese invention patent with publication number CN115449842A discloses a lead-doped low-temperature synthesized yttrium ruthenate catalyst and its preparation method and application. The patent uses a one-pot method to mix ruthenium salt, yttrium salt and lead salt, and then dry and calcine at a relatively low temperature under the action of oxidizing acid and water-soluble organic matter to obtain a lead-doped low-temperature synthesized yttrium ruthenate catalyst. The main purpose of this method is to reduce the temperature and reaction time of the calcination treatment by doping lead in the catalyst, but it does not involve the multi-level pore structure of the catalyst, nor does it explore the mechanism of the catalytic reaction. In addition, there is the problem of catalyst sintering during the heat treatment process of the traditional calcination method (muffle furnace, tubular furnace). Summary of the invention

[0005] The purpose of the present invention is to provide a rapid preparation method of a porous ruthenate pyrochlore catalyst doped with calcium ions, which can solve the problems of long reaction time, huge energy consumption, poor composition modulation, sintering and low catalytic activity in the traditional pyrolysis process of preparing ruthenate pyrochlore catalysts. The method optimizes the geometric configuration and electronic structure of Ru in the ruthenate catalyst, improves the intrinsic activity of Ru, and exhibits efficient acidic OER performance, which has broad industrial prospects.

[0006] To achieve this object, the technical solution of the present invention is:

[0007] A method for rapidly preparing a calcium ion-doped porous ruthenate pyrochlore catalyst comprises the following steps:

[0008] (1) adding yttrium nitrate, ruthenium nitrate, citric acid and perchloric acid into deionized water, stirring and mixing to obtain a mixed solution;

[0009] (2) stirring the mixed solution at 70-95° C. for 24-36 hours to obtain a gel;

[0010] (3) mixing the gel with nano-calcium carbonate and grinding them into powder, then placing the powder in a groove of a graphite sample stage of a Joule heating device, and then performing Joule heat treatment in an air atmosphere to obtain a precursor;

[0011] (4) Add the precursor to an aqueous acetic acid solution, react at 50-80° C. for 2-4 hours, and obtain a calcium ion-doped porous ruthenate pyrochlore catalyst by centrifugation, washing, and vacuum drying.

[0012] The inventors found in the experimental process of step (2) that when the reaction temperature is lower than 70°C, no gel can be obtained after stirring the reaction for 36 hours; when the temperature exceeds 95°C, the mixed solution will boil after long-term heating, causing the solution to splash, which is somewhat dangerous. Therefore, the reaction conditions should be properly controlled.

[0013] Furthermore, in step (1), the usage ratio of yttrium nitrate, ruthenium nitrate, citric acid, perchloric acid and deionized water is: 1mmol:1-1.6mmol:10-20mmol:1-2mmol:100mL.

[0014] Furthermore, in step (3), the particle size of the nano calcium carbonate is 20-50 nm.

[0015] Furthermore, in step (3), the ratio of the amount of gel to the amount of nano-calcium carbonate is 1g:1-5g.

[0016] Furthermore, in step (3), the conditions of Joule heat treatment are: heat treatment temperature 700-1600°C, heating rate 2000-3000°C / s, and Joule heat treatment times 5-10 times. Joule heat treatment is heating from room temperature to the target temperature, and then naturally cooling to room temperature, which is represented as one time.

[0017] Furthermore, in step (4), the concentration of the acetic acid aqueous solution is 30-70% by mass of acetic acid; and the ratio of the precursor to the acetic acid aqueous solution is 0.2-0.5 g:50 mL.

[0018] Furthermore, in step (4), the washing conditions are: washing with deionized water and ethanol three to five times respectively; and the vacuum drying conditions are: drying temperature 50-80° C., and drying time 10-24 h.

[0019] Another object of the present invention is to provide an application of a calcium ion-doped porous ruthenate pyrochlore catalyst prepared by the above method, which is used as an electrochemical catalyst in oxygen evolution reaction (OER) under acidic conditions.

[0020] The beneficial effects of the present invention are:

[0021] (1) Compared with the traditional high-temperature calcination method, the Joule heat treatment technology of the present invention has simple equipment operation, high catalyst preparation efficiency, and low energy consumption, which helps to inhibit the collapse of the pore structure at high temperature while ensuring that the catalyst has high activity and stability.

[0022] (2) Compared with the traditional thermal decomposition and calcination method, the Joule heat treatment technology of the present invention can inhibit the sintering of the ruthenate pyrochlore catalyst and form a richer pore structure; in particular, the use of nano-calcium carbonate as a structure modification additive can decompose and produce a large amount of CO2 during the calcination process of the Joule heat treatment technology, which can further inhibit the sintering of the ruthenate pyrochlore catalyst and enrich the porous structure. It has a good pore-forming effect when used in conjunction with the Joule heat treatment technology; in addition, the instantaneous high temperature during the Joule heat treatment technology can promote calcium ions to enter the lattice of the ruthenate pyrochlore, promote the synergistic effect of Ca and Ru, optimize the geometric configuration and electronic structure of Ru in the ruthenate catalyst, and then improve the intrinsic activity of Ru. The catalyst exhibits excellent acidic OER performance.

[0023] (3) The post-treatment method of the acetic acid aqueous solution of the present invention not only helps to remove excess calcium carbonate, but also helps to form mesopores and macropores. The removal of calcium carbonate helps to improve the conductivity, and the multi-level pore structure of mesopores and macropores helps to desorb oxygen products, which together improves the electrochemical catalytic effect. In addition, the use of acetic acid aqueous solution in combination with Joule heat treatment technology has a synergistic effect and has a better pore-forming effect.

[0024] (4) The calcium ion-doped porous ruthenate pyrochlore catalyst of the present invention has outstanding performance in oxygen evolution reaction under acidic conditions, and its specific surface area and pore size range are 29.24-33.37 m 2 / g, 3-65nm. In 0.1M HClO4 aqueous solution, 10 mA·cm -2 Under current density, the OER overpotential of the catalyst is 202.1-235.4 mV, which is far higher than the 321.5 mV overpotential of commercial IrO2 under the same conditions, and has broad prospects for industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a nitrogen total adsorption test (N2-BET) diagram of the calcium ion-doped porous ruthenate pyrochlore catalyst of Example 1 and Comparative Examples 1-2;

[0026] Figure 2 This is a transmission electron microscope energy spectrum (TEM-Mapping) image of the calcium ion-doped porous ruthenate pyrochlore catalyst of Example 1;

[0027] Figure 3 X-ray photoelectron spectroscopy (XPS) graphs of the porous ruthenate pyrochlore catalysts doped with calcium ions in Example 1 and Comparative Example 1;

[0028] Figure 4 This is a linear sweep voltammetry (LSV) test graph of the calcium ion-doped porous ruthenate pyrochlore catalyst prepared in Example 1 for oxygen evolution reaction. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that a person skilled in the art can better understand and implement the present invention, but the protection scope of the present invention is not limited thereto.

[0030] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available materials; unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those skilled in the art.

[0031] In a specific embodiment of the present invention, the Joule heating device used is composed of a gas circuit device, a vacuum pump, a graphite sample stage, a temperature control system, and a data acquisition system. The model is CIS-JH3.3-P, the output voltage is 0-40V, the output current is 0-500A, the temperature measurement range is 0-3000℃, the power supply is 380V / 30A, and the current ramp time is 1ms. Example 1

[0032] (1) Add 1 mmol of yttrium nitrate, 1.5 mmol of ruthenium nitrate, 16 mmol of citric acid, and 1.5 mmol of perchloric acid into 100 mL of deionized water, stir and mix well to obtain a mixed solution;

[0033] (2) stirring the mixed solution at 90°C for 30 hours to obtain a gel;

[0034] (3) 1 g of the gel was mixed with 3 g of nano-calcium carbonate with a particle size of 20 nm and ground into powder, and then the powder was placed in the groove of the graphite sample stage of the Joule heating device, and then Joule heat treatment was performed 8 times in an air atmosphere, with the Joule heat treatment temperature of 950°C and the Joule heat treatment heating rate of 2500°C / s to obtain a precursor;

[0035] (4) 0.3 g of the precursor was added to 50 mL of 50% acetic acid aqueous solution and reacted at 70 °C for 3 h. The catalyst was centrifuged, washed four times with deionized water and ethanol, and dried in vacuum at 70 °C for 18 h to obtain a calcium ion-doped porous ruthenate pyrochlore catalyst. Example 2

[0036] (1) Add 1 mmol of yttrium nitrate, 1 mmol of ruthenium nitrate, 10 mmol of citric acid, and 1 mmol of perchloric acid into 100 mL of deionized water, stir and mix well to obtain a mixed solution;

[0037] (2) stirring the mixed solution at 70°C for 36 hours to obtain a gel;

[0038] (3) 1 g of the gel was mixed with 1 g of nano-calcium carbonate with a particle size of 50 nm and ground into powder, and then the powder was placed in the groove of the graphite sample stage of the Joule heating device, and then Joule heat treatment was performed 5 times in an air atmosphere, with the Joule heat treatment temperature of 1600°C and the Joule heat treatment heating rate of 2000°C / s to obtain a precursor;

[0039] (4) 0.2 g of the precursor was added to 50 mL of a 30% acetic acid aqueous solution and reacted at 50 °C for 4 h. The mixture was centrifuged, washed three times with deionized water and ethanol, and vacuum dried at 50 °C for 24 h to obtain a calcium ion-doped porous ruthenate pyrochlore catalyst. Example 3

[0040] (1) Add 1 mmol of yttrium nitrate, 1.6 mmol of ruthenium nitrate, 20 mmol of citric acid, and 2 mmol of perchloric acid into 100 mL of deionized water, stir and mix well to obtain a mixed solution;

[0041] (2) stirring the mixed solution at 95°C for 24 hours to obtain a gel;

[0042] (3) 1 g of the gel was mixed with 5 g of nano-calcium carbonate with a particle size of 30 nm and ground into powder. The powder was then placed in the groove of a graphite sample stage of a Joule heating device, and then subjected to Joule heat treatment 10 times in an air atmosphere at a Joule heat treatment temperature of 700 °C and a Joule heat treatment heating rate of 3000 °C / s to obtain a precursor.

[0043] (4) 0.5 g of the precursor was added to 50 mL of 70% acetic acid aqueous solution and reacted at 80 °C for 2 h. The product was centrifuged, washed five times with deionized water and ethanol, and vacuum dried at 80 °C for 10 h to obtain a calcium ion-doped porous ruthenate pyrochlore catalyst. Example 4

[0044] (1) Add 1 mmol of yttrium nitrate, 1.4 mmol of ruthenium nitrate, 15 mmol of citric acid, and 1.4 mmol of perchloric acid into 100 mL of deionized water, stir and mix well to obtain a mixed solution;

[0045] (2) stirring the mixed solution at 85°C for 32 hours to obtain a gel;

[0046] (3) 1 g of the gel was mixed with 2.5 g of nano-calcium carbonate with a particle size of 25 nm and ground into powder. The powder was then placed in the groove of the graphite sample stage of a Joule heating device, and then subjected to Joule heat treatment 8 times in an air atmosphere at a Joule heat treatment temperature of 1050 °C and a Joule heat treatment heating rate of 2500 °C / s to obtain a precursor.

[0047] (4) 0.25 g of the precursor was added to 50 mL of 50% acetic acid aqueous solution and reacted at 70 °C for 3 h. The product was centrifuged, washed four times with deionized water and ethanol, and dried in vacuum at 70 °C for 18 h to obtain a calcium ion-doped porous ruthenate pyrochlore catalyst. Comparative Example 1

[0048] The difference between Comparative Example 1 and Example 1 is that no nano calcium carbonate is added in step (2), and the other steps remain unchanged. Comparative Example 2

[0049] The difference between Comparative Example 2 and Example 1 is that the heating device in step (3) is different, and the other steps remain unchanged. The specific operation is as follows:

[0050] 1 g of gel was mixed with 3 g of nano-calcium carbonate with a particle size of 20 nm and ground into powder. The powder was then placed in a tubular furnace and calcined in an air atmosphere at a calcination temperature of 950°C and a heating rate of 10°C / min. The reaction was kept warm for 2 hours to obtain a precursor. Comparative Example 3

[0051] The difference between Comparative Example 3 and Example 1 is that no perchloric acid is added in step (1), and the other steps remain unchanged.

[0052] During the experiment, it was found that when no perchloric acid was added, the mixed solution would not turn into a gel state after long-term stirring (3 days). Therefore, perchloric acid is the key factor in the formation of gel. Comparative Example 4

[0053] The difference between Comparative Example 4 and Example 1 is that in step (4), there is no treatment with aqueous acetic acid solution, and the mixture is only immersed in water, while the other conditions remain unchanged. Comparative Example 5

[0054] The difference between Comparative Example 1 and Example 1 is that the particle size of the nano-calcium carbonate in step (3) is different, and the other parameters remain unchanged. The nano-calcium carbonate with a particle size of 20 nm is replaced with nano-calcium carbonate with a particle size of 100 nm.

[0055] Application Example 1

[0056] 4 mg of the catalyst prepared in the embodiment or comparative example or commercial IrO2 and 1 mg of commercial carbon black were added to an ethanol-Nafion mixed solution (a mixture of 0.48 mL of ethanol and 0.02 mL of 0.5% Nafion solution), and after ultrasonic treatment for 2 h, a uniformly dispersed catalyst solution was obtained; 0.01 mL of the catalyst solution was measured with a pipette and dropped onto a glassy carbon electrode, and the catalyst-modified glassy carbon electrode was obtained after natural air drying; the electrochemical test was carried out on a CHI760E electrochemical workstation, with the catalyst-modified glassy carbon electrode as the working electrode, a graphite rod as the counter electrode, a saturated calomel as the reference electrode, and a 0.1 M HClO4 aqueous solution as the electrolyte, and a linear sweep voltammetry (LSV) test of the oxygen evolution reaction was carried out, and the test results are shown in Table 1.

[0057] The porous ruthenate pyrochlore catalysts doped with calcium ions obtained in Examples 1-4, Comparative Examples 1-2 and Comparative Examples 4-5 were subjected to a nitrogen total adsorption (N2-BET) test. The test results are shown in Table 1, wherein the N2-BET test includes a specific surface area test and a pore size distribution (NLDFT model total pore distribution) test.

[0058]

[0059] From the comparison of Examples 1-4 and Comparative Example 1 in Table 1, it can be seen that the nano calcium carbonate powder helps to improve the pore size distribution and specific surface area of ​​the catalyst, thereby affecting the catalytic effect; from the comparison of Examples 1-4 and Comparative Example 2, it can be seen that the influence of calcination in a tubular furnace on the specific surface area and pore size of the material is much lower than that of the Joule heat heating device, therefore, the calcium ion-doped porous ruthenate pyrochlore catalyst of Comparative Example 2 has a poor catalytic effect; from the comparison of Examples 1-4 and Comparative Example 4, it can be seen that the acetic acid aqueous solution mainly affects the pore size of the material and removes the excess Calcium carbonate, the multi-level pore structure is helpful for the desorption of oxygen products. The presence of calcium carbonate affects the conductivity of the catalyst. Therefore, the calcium ion-doped porous ruthenate pyrochlore catalyst of Comparative Example 4 has a poor catalytic effect. By comparing Examples 1-4 with Comparative Example 5, it can be seen that the particle size of nano-scale calcium carbonate also affects the catalytic effect. This is mainly because the particles with larger particle sizes are not calcined sufficiently and the acid treatment process of the acetic acid aqueous solution is not completely reacted, resulting in a large amount of calcium carbonate in the catalyst, which affects the conductivity and pore size distribution of the catalyst, and thus the catalytic effect is reduced.

[0060] Figure 1The nitrogen total adsorption test (N2-BET) diagram of the calcium ion-doped porous ruthenate pyrochlore catalyst prepared in Example 1 and Comparative Examples 1-2. It can be seen from the figure that the specific surface area of ​​Example 1 is 33.37 m 2 / g, significantly higher than that of comparative example 1 (14.79m 2 / g) and Comparative Example 2 (19.06m 2 / g). This is mainly because the nano calcium carbonate additive will decompose and produce a large amount of CO2 during the high temperature process, which synergistically inhibits the sintering of ruthenate at high temperature with the Joule heat treatment technology (rapid temperature rise and fall characteristics) and forms a large specific surface area and rich pore structure.

[0061] Figure 2 This is a transmission electron microscope energy spectrum (TEM-Mapping) diagram of the calcium ion-doped porous ruthenate pyrochlore catalyst prepared in Example 1. It can be seen from the figure that the three elements Ca, Y and Ru are evenly distributed, indicating that the calcium ions enter the lattice of the ruthenate pyrochlore.

[0062] Figure 3 X-ray photoelectron spectroscopy (XPS) diagrams of the calcium ion-doped porous ruthenate pyrochlore catalysts prepared in Example 1 and Comparative Example 1. As can be seen from the figure, compared with Comparative Example 1, the XPS characteristic peak of Ru in Example 1 moves to a high binding energy, indicating that the valence state of Ru in Example 1 increases. Therefore, the calcium ion-doped porous ruthenate pyrochlore catalyst of Example 1 is more conducive to combining with the intermediate product in the OER reaction process and promoting the performance of OER, because Example 1 has a high-valence Ru.

[0063] Figure 4 This is a linear sweep voltammetry (LSV) performance test diagram of the oxygen evolution reaction of the calcium ion-doped porous ruthenate pyrochlore catalyst prepared in Example 1. Figure 4 Combined with the results in Table 1, it can be seen that the modified electrode in Example 1 has a -2 The overpotential required at the current density is only 202.1mV, which is much lower than that of commercial IrO2 (321.5mV@10mA•cm -2), indicating that the catalyst has more prospects for industrial application. At the same time, the performance of the catalyst prepared without using nano calcium carbonate additives (Comparative Example 1) or directly using the traditional calcination method (Comparative Example 2) is far inferior to that of the catalyst prepared with nano calcium carbonate as an additive combined with Joule heat treatment technology (Example 1). The fundamental reason for this difference is that the nano calcium carbonate additive will decompose and produce a large amount of CO2 during the high temperature process, and the advantage of the rapid temperature rise and fall of Joule heat synergistically inhibits the sintering of ruthenate at high temperature and forms a rich multi-level pore structure, which is not only conducive to the exposure of active sites, but also can promote the release of OER reaction product O2. In addition, this method can also promote calcium ions to enter the lattice of ruthenate pyrochlore, thereby effectively modulating the composition of ruthenate, optimizing the geometric configuration and electronic structure of Ru in the ruthenate catalyst, and improving the intrinsic activity of Ru. The increased number of active sites and the synergistic intrinsic activity formed by Ca and Ru jointly improve the acidic OER performance of the catalyst.

[0064] The above embodiments are intended to illustrate the essential content of the present invention, but are not intended to limit the protection scope of the present invention. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and protection scope of the technical solution of the present invention.

Claims

1. A method for rapidly preparing a porous ruthenate pyrochlore catalyst doped with calcium ions, characterized in that: The following steps are involved: (1) adding yttrium nitrate, ruthenium nitrate, citric acid and perchloric acid into deionized water, stirring and mixing to obtain a mixed solution; (2) stirring the mixed solution at 70-95° C. for 24-36 hours to obtain a gel; (3) mixing the gel with nano-calcium carbonate and grinding them into powder, then placing the powder in a groove of a graphite sample stage of a Joule heating device, and then performing Joule heat treatment in an air atmosphere to obtain a precursor; the particle size of the nano-calcium carbonate is 20-50 nm; (4) Add the precursor to an aqueous acetic acid solution, react at 50-80° C. for 2-4 hours, and obtain a calcium ion-doped porous ruthenate pyrochlore catalyst by centrifugation, washing, and vacuum drying.

2. The rapid preparation method of the calcium ion-doped porous ruthenate pyrochlore catalyst according to claim 1, characterized in that: In the step (1), the usage ratio of yttrium nitrate, ruthenium nitrate, citric acid, perchloric acid and deionized water is: 1mmol:1-1.6mmol:10-20mmol:1-2mmol:100mL.

3. The rapid preparation method of the calcium ion-doped porous ruthenate pyrochlore catalyst according to claim 1, characterized in that: In the step (3), the ratio of the amount of gel to the amount of nano calcium carbonate is 1g:1-5g.

4. The rapid preparation method of the calcium ion-doped porous ruthenate pyrochlore catalyst according to claim 1, characterized in that: In the step (3), the conditions of the Joule heat treatment are: heat treatment temperature 700-1600°C, heating rate 2000-3000°C / s, and Joule heat treatment times 5-10 times.

5. The rapid preparation method of the calcium ion-doped porous ruthenate pyrochlore catalyst according to claim 1, characterized in that: In the step (4), the concentration of the acetic acid aqueous solution is 30-70% by mass of acetic acid; and the ratio of the precursor to the acetic acid aqueous solution is 0.2-0.5 g:50 mL.

6. The rapid preparation method of the calcium ion-doped porous ruthenate pyrochlore catalyst according to claim 1, characterized in that: In the step (4), the washing conditions are: washing with deionized water and ethanol three to five times respectively; the vacuum drying conditions are: drying temperature 50-80°C, drying time 10-24h.

7. Use of a porous ruthenate pyrochlore catalyst doped with calcium ions prepared by the preparation method according to any one of claims 1 to 6, characterized in that: It was used as an electrochemical catalyst for oxygen evolution reaction under acidic conditions.

Citation Information

Patent Citations

  • Lead-doped low-temperature synthesized yttrium ruthenate catalyst as well as preparation method and application thereof

    CN115449842A

  • Bismuth-doped yttrium ruthenate and preparation method and oxygen evolution application thereof

    CN110227452A

  • Calcium-doped yttrium ruthenate and preparation method and application to electrochemical device thereof

    CN110745881A